Chemical constituents, antioxidant and cytotoxicity properties of Rhodomyrtus Tomentosa root extracts - Roziasyahira, Mutazah (2017)
A study was carried out on the chemical constituents, antioxidant and cytotoxicity properties of Rhodomyrtus tomentosa root extracts. Solvent–solvent extraction, fractionation and separation using different chromatographic techniques (column chromatography and thin layer chromatography) were used for isolation of pure compounds. The chemical constituents of the roots of R. tomentosa were subjected to ultra-high performance liquid chromatography-quadrupole time-of-flight/mass spectrometry (UPLC-QToF/MS) for the determination of compound composition present in the plant. The potential cytotoxicity of R. tomentosa extracts from different solvents were evaluated in vitro on HepG2, MCF-7 and HT 29 cell lines and antioxidant activity was monitored by radical scavenging assay (DPPH), copper reducing antioxidant capacity (CUPRAC) and β-carotene bleaching assay. Each extract from R. tomentosa inhibited proliferation on all cancer cell lines in a concentration-dependant manner. According to the IC50 obtained, the results exhibited significant activity against cancer cell line under 72h incubation with IC50 value < 30 μg/mL for ethyl acetate on HepG2, methanol and ethyl acetate on both MCF-7 and HT 29. Methanol extracts show significant antioxidant activities in DPPH, CUPRAC and β-carotene due to the presence of high total flavonoid and total phenolic content of R. tomentosa. Bioassay guided fractionation of ethyl acetate extract led to the isolation of lupeol and fractionation of chloroform extract led to the isolation of β-sitosterol. The structure of the isolated compounds were elucidated by spectroscopic methods such as 1D (1H, 13C, DEPTQ), 2D (COSY, HMQC, HMBC) NMR, MS, UV, FTIR and also by comparison with the literature. Collectively, the results show that R. tomentosa is a potential source of antioxidant and cytotoxicity and identified lupeol being a possible promising chemical lead for further development as anticancer agent.